Perception of attractive and unattractive face groups is driven by distinct spatial frequencies - Ying, Haojiang (2022)
Our visual system is able to extract information on facial attractiveness from groups of faces that contain both coarse and detailed information. This raises the question: What information is extracted from a face group? Is the attractiveness perception of multiple faces driven by high or low spatial frequency that can highlight the local or global information of the faces, respectively? In the first experiment, we adapted participants to four unattractive faces with full bandwidth (FB), high spatial frequency (HSF), and low spatial frequency (LSF). We observed significant aftereffects in the HSF faces adaptation condition, which suggests that the perception of multiple unattractive faces is largely driven by HSF information. In the second experiment, we found a similar but different pattern in the direct-rating tasks, suggesting distinct perception mechanisms in unattractive versus attractive faces. In the third experiment, both the adaptation and direct-rating paradigms suggested that perception of multiple attractive faces is largely driven by LSF information. Overall, results from the three experiments together found that perception of multiple attractive and unattractive faces depends on visual information from different spatial frequencies, suggesting distinctive mechanisms in processing attractive and unattractive groups of faces.